Mental Health in the Family Business: A Conceptual Model and a Research Agenda. (January 2020) - Miller, Danny; Wiklund, Johan; Yu, Wei
Mental health issues are affecting not only families worldwide but also numerous family businesses. Anecdotal evidence suggests that the uniqueness of the family business may be a double-edged sword generating both benefits and drawbacks for business families dealing with mental disorders. Building on the socioemotional wealth (SEW) perspective of family business, the ABCX model of family coping, and work–family interface literature, we develop a theoretical model to suggest how MDs interact with family and family business resources to influence the dynamics between families and their firms, and the outcomes from those dynamics. A research agenda is then proposed.